PENGARUH KOMPETENSI SOSIAL GURU DAN POLA ASUH ORANG TUA TERHADAP IKLIM BELAJAR DI KELAS IX SMP MUHAMMADIYAH SERPONG, TANGERANG SELATAN, BANTEN - Saifuddin Zuhri; Mutmainah Mutmainah (el-Moona: Jurnal Ilmu Pendidikan Islam, 2019)
This study aims to determine and test empirical data related to the Social Competence of Teachers and Parenting Parents to Learning Climate separately or simultaneously. In this study the authors used a survey method, with correlational techniques and simple and multiple regression analysis. The sample of this study was 76 respondents or used the entire population of class IX students of SMP Muhammadiyah Serpong. Data collection techniques using questionnaires, observation, and documentary studies. Data analysis techniques used are descriptive analysis models, correlation coefficients, simple regression analysis and multiple regression. The type of analysis used is correlation analysis and simple regression and multiple regression which are described descriptively. The results of this study indicate that: First, there is a positive and significant influence of Teacher's Social Competence on Learning Climate in Class IX of SMP Muhammadiyah Serpong. This is evidenced by the results of the correlation coefficient of 0.303 and the coefficient of determination R2 of 0.092. Second, there is a positive and significant influence of Parenting Parents on Learning Climate in Class IX SMP Muhammadiyah Serpong. This is evidenced by the results of the correlation coefficient (r) of 0.068 and the coefficient of determination R2 of 0.005. Third, there is a positive and significant influence of Teacher's Social Competence and Parenting Parents together on the Learning Climate in Class IX of SMP Muhammadiyah Serpong. This is evidenced by the magnitude of the influence of the coefficient of determination R2 of 0.319.